2010
DOI: 10.1002/lary.21084
|View full text |Cite
|
Sign up to set email alerts
|

The surgical management of goiter: Part I. preoperative evaluation

Abstract: Goiter size is associated with increasing symptoms. Tracheal compression but not deviation was related to shortness of breath. Females and patients with a positive family history of goiter have an increased risk of goiter recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 24 publications
5
30
2
Order By: Relevance
“…A study on patients with substernal goiter investigating dysphagia and esophageal compression, detected by computed tomography, did not identify any correlation, but the study was characterized by a small number of highly selected patients [24]. Other studies found positive correlations between esophageal compression and symptoms [22, 23], but definitions of esophageal compression and deviation were lacking, thereby hindering meaningful comparisons with our results. A retrospective study on 198 patients found a positive correlation (of unreported magnitude) between preoperative dysphagia and image findings, without defining what these findings represented [23].…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…A study on patients with substernal goiter investigating dysphagia and esophageal compression, detected by computed tomography, did not identify any correlation, but the study was characterized by a small number of highly selected patients [24]. Other studies found positive correlations between esophageal compression and symptoms [22, 23], but definitions of esophageal compression and deviation were lacking, thereby hindering meaningful comparisons with our results. A retrospective study on 198 patients found a positive correlation (of unreported magnitude) between preoperative dysphagia and image findings, without defining what these findings represented [23].…”
Section: Discussioncontrasting
confidence: 44%
“…Other studies found positive correlations between esophageal compression and symptoms [22, 23], but definitions of esophageal compression and deviation were lacking, thereby hindering meaningful comparisons with our results. A retrospective study on 198 patients found a positive correlation (of unreported magnitude) between preoperative dysphagia and image findings, without defining what these findings represented [23]. A previous study by our group found no major association between esophageal motility disturbances and swallowing difficulties in patients with goiter [27], but that study may have been underpowered as it included only 33 patients.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…It was recently demonstrated that tracheal compression but not deviation was related to shortness of breath. 22 The displacement of the trachea is always accompanied by a certain amount of curving of the trachea upon itself, and frequently by some twisting of the trachea upon its long axis. In very rare cases the trachea is displaced directly or obliquely forwards.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional cases of overt hyperthyroidism have also been reported. A retrospective study by Shin et al reported a positive correlation between thyroid size and presence of shortness of breath, globus sensation, and symptoms of hyperthyroidism 3 . This study, however, did not find a correlation between goiter size and presence of dysphagia, local discomfort, changes in voice, hemoptysis, or symptoms of hypothyroidism.…”
Section: Introductionmentioning
confidence: 98%